Automatic Detection of Sports Injuries Based on Multimedia Intelligent 3D Images - Chunmei Liu; Longhui Cao (Advances in Multimedia)
With the concept of quality education put forward, students’ sports activities have received extensive attention from society. As a result, sports injuries among students during sports have also aroused widespread concern, so it is an irreversible trend to detect sports injuries. The development of multimedia intelligent 3D image technology also provides technical support for sports injury detection, which makes it possible to automatically detect sports injuries. In this paper, an automatic detection system for sports injuries was designed based on multimedia intelligent three-dimensional image technology, and the related content was evaluated. In the investigation of the parts of students’ sports injuries, it was concluded that the injury rate of the students’ ankle joints was the highest; in the investigation of the types of sports injuries among students, it was concluded that students were more likely to suffer from joint sprains; in the project investigation of students’ sports injuries, it was concluded that students were more prone to sports injuries in ball games with a large amount of exercise; in the investigation of the causes of students’ sports injuries, it was concluded that the main reasons for students’ sports injuries were physical insufficiency and a bad venue environment; in terms of the performance evaluation of the sports injury detection system, it was concluded that the accuracy, effectiveness, authenticity, and efficiency of the sports injury automatic detection system based on multimedia intelligent three-dimensional image processing technology had been improved to different degrees compared with the traditional sports injury detection methods. Therefore, the detection efficiency of the sports injury automatic detection system proposed in this paper was improved by 5.7% compared with the traditional sports injury detection method.